Real-time prediction of wear morphology and coefficient of friction using acoustic signals and deep neural networks in a tribological system - Tian, Yang; Zheng, Bohao; Khan, Muhammad; Yang, Yifan (MDPI, 2025)
Predicting real-time wear depth distribution and the coefficient of friction (COF) in tribological systems is challenging due to the dynamic and complex nature of surface interactions, particularly influenced by surface roughness. Traditional methods, relying on post-test measurements or oversimplified assumptions, fail to capture this dynamic behavior, limiting their utility for real-time monitoring. To address this, we developed a deep neural network (DNN) model by integrating experimental tribological testing and finite element method (FEM) simulations, using acoustic signals for non-invasive, real-time analysis. Experiments with brass pins (UNS C38500) of varying surface roughness (240, 800, and 1200 grit) sliding against a 304 stainless steel disc provided data to validate the FEM model and train the DNN. The DNN model predicted wear morphology with accuracy comparable to FEM simulations but at a lower computational cost, and the COF with relative errors below 10% compared to experimental measurements. This approach enables real-time monitoring of wear and friction, offering significant benefits for predictive maintenance and operational efficiency in industrial applications.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; Bioengineering; 4004 Chemical engineering; wear; friction; DNN; friction noise